Constraints to Sustainable Tourism Development in Bojonegoro Regency - Suci Megawati; Noer Falaq Al Amin; Melda Fadiyah Hidayat; Hety Mashita (Borong Newinera Publisher, 2023)
The development of sustainable tourism must provide economic, social, and cultural benefits to the communities around the destination. In developing countries, tourism development is still an obstacle that does not follow the principles of sustainable tourism development. This research aims to examine the constraints of sustainable tourism development in Bojonegoro Regency. This research used a mixed method approach with participants using the purposive sampling method and respondents using the slovin method conducted at the Tourism Office and eight Tourism Villages in Bojonegoro Regency. Data collection techniques using Desk Study, Observation, Survey, FGD and Indepth Interview. Data analysis techniques using descriptive statistics and grounded theory analysis. The results showed the constraints of sustainable tourism development in Bojonegoro Regency in terms of; (1). Ecological aspects show the highest average answer neutral/middle results in this case neither good nor bad at 48.87%; (2). Aspects of macroeconomic sustainability showed the highest average answer was good at 69.47%; (3). The social and cultural sustainability aspect shows the highest average answer is good by 65.80%; (4). The political aspect shows the highest average answer was good by 60.44%; (5). The defense and security aspect showed the highest average answer was good by 60.33%. It is recommended to improve ecological sustainability by providing guarantees in maintaining the integrity of the environmental order, sustainability in utilizing existing resources, and environmental management that prioritizes the balance of the surrounding ecosystem.